WAR TRAUMA IN THE CONTEMPORARY SERBIAN NOVEL: THE HOUSE OF REMEMBRANCE AND OBLIVION BY FILIP DAVID, THE DELUSION OF ST. SEBASTIAN BY VLADIMIR TABAŠEVIĆ, THE DOG AND THE DOUBLE BASS BY SAŠA ILIĆ (Philological Studies, 2020)
The paper discusses the literary shaping of war traumas in the novels “The House of Remembrance and Oblivion” by Filip David, “The Delusion of St. Sebastian” by Vladimir Tabašević and “The Dog and the Double Bass” by Saša Ilić. The manner in which the Holocaust influences the life of Albert Weiss and the lives of other characters, decades after World War II, and the mystical contemplation of the meaning of evil stand out as the most important themes of David’s novel. The interpretation of “The Delusion of St. Sebastian” proceeds via the protagonist Karl and his attitude to the language he learned during the war. The war induces dissociative identity disorder, the protagonist’s adoption and subsequent overcoming of the victim’s position. The analysis of Ilić’s work focuses on the protagonist of the novel “The Dog and the Double Bass”, Filip Isaković, and his post-traumatic stress disorder, as well as psychiatric and anti-psychiatric treatment methods.
Keywords: The House of Memory and Forgetting; Saint Sebastian’s Delusion; The Dog and the Double Bass; Holocaust; Civil war in Yugoslavia; trauma; victim; memory; anti-psychiatry; literary motivation